THE EFFECTIVENESS OF ROLE-PLAY TO IMPROVE STUDENT'S SPEAKING ACHIEVEMENT - Maulana, Irfan; Lolita, Yuri (ELite Journal : International Journal of Education, Language and Literature, 2023)
The Role-play method is important to students’ growth in understanding real-life illustrations by pretending as someone else or some scenario. The study aimed to demonstrate whether the Role-play method affects students’ speaking achievement. The research was carried out in the SMP Raden Rahmat Wonokromo for seventh-year students in the academic year 2020/2021, which included 31 students. The data are collected using a few methods, including pre-tests and post-tests. To dissect the quantitative information, an expert used the highest and lowest scores, as well as means and standard deviations. According to the questionnaire results, the role-playing method can improve students’ speaking ability by 11.8%, while the traditional method is only 5.2%. The students are mainly shy to speak English, making them stutter or slower, but they are still enthusiastic about doing some Role-playing. There were differences between the pre-test and the post-test of about 72.5 and 84.3 in the experimental class, respectively. According to the calculation, the ttest is higher than the ttable, 4.304 > 1.697. In other words, the hypothesis alternative (Ha) has been accepted. The role-play practice could effectively show the students’ concern about their English-speaking achievements. It tends to be expressed that showing speaking using Role-play truly impacts students’ English-speaking achievement.